ҚАРАҚАЛПАҚСТАН ОЙКОНИМЛЕРИНДЕ КӘСИПЛИК ЛЕКСИКАНЫҢ ЭТНОМӘДЕНИЙ СЫПАТЫ - Қурбанов, М.Д. (SCIENCE and SOCIETY, 2022)
The article analyzes the ethno-cultural and semantic features of professional vocabulary in the oikonymy of Karakalpakstan. The types of occupations of local residents, the reflection of their vocabulary in toponyms, the importance of studying this type of oikonyms are explained in detail. Toponymic and ethnographic data are used.